Penerapan PECS Pada Autism Spectrum Disorder Usia 6 Tahun : Studi Kasus Tunggal - Nining Lestari; Yusi Lusia Ningsih; Alfa Reza Antafani (Jurnal Terapi Wicara, 2025)
Background: Communication is very important in a person's life to be able to express what they want, so that they can communicate with their interlocutors, both verbally and non-verbally. Communication can be hampered due to certain disorders, one of which is autism. Autism is a pervasive developmental disorder in which there are problems with cognition, social emotions, behavior, difficulty interacting with others, and a greater interest in one's own world. Limitations in social and cognitive interactions can affect quality of life. Objective: The objective is to obtain an overview of speech language abilities in autism and to determine the application of the Picture Exchange Communication System (PECS) method in autism spectrum disorder. Method: This study used a single-subject experiment or Single Subject Research. The participant was a 6-year-old boy. Data collection was conducted through interviews with the client's parents, direct observation of the client, tests, and document studies. Results: The client's diagnosis is autism spectrum disorder, speech impairment, auditory perception impairment, and motor delay. The use of the PECS method to improve verbal communication skills was unsuccessful. Conclusion: The importance of awareness and early intervention for disorders in children. Recommendation: It is necessary to pay attention to the planning of therapy implementation, including the materials used, therapy variations, and the client's condition, in order to achieve optimal therapy outcomes.